SANKSI HUKUM TERHADAP PELAKU GAME ONLINE DITINJAU DARI HUKUM ISLAM DAN HUKUM NASIONAL - Gunawan, Hendra; Yanti, Sri Afrida (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
This paper aims to analyze legal sanctions for online game players, especially domino or scatter online games. Every act of gambling is prohibited by laws and regulations, as stipulated in Article 303 of the Criminal Code. The reasons for playing games are very diverse, some are to fill the void of time but can be haram (not allowed), if there is an element of betting (gambling). This research is a normative-juridical legal research, so to answer this question the author digs from literature and electronic media that discusses the intricacies of domino or scatter games, then analyzes from the point of view of Islamic law, about the elements why legal sanski does not run officially. The results of this study show that legal sanctions for online gambling players can be sentenced to imprisonment for 10 years (Article 30 of the Criminal Code). While Article 303 BIS regulates unlicensed gambling. "Any person who without permission holds or gives the opportunity to play gambling. A maximum prison sentence of 4 years or a maximum fine of Rp 10 million". Meanwhile, Law No. 7 of 1974 concerning the Regulation of Gambling affirms the prohibition of all forms of gambling and strengthens penalties for violations. Strengthen existing sanctions in the Criminal Code, including the possibility of additional penalties in accordance with the enforcement policy. While Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE) explains that Article 27 Paragraph (2) concerning the prohibition of distribution of electronic information containing gambling content. "Any person intentionally and without rights distributes and/or transmits and/or makes accessible Electronic Information that has gambling content. A maximum prison sentence of 6 years and/or a maximum fine of IDR 1 billion". While QS. Al-Baqarah Verse 219 and QS. Al-Maidah Verse 90 explains that the act of scatter type online games is strictly forbidden, because there are elements of ta'jir or maisir. It can be concluded that the legal sanctions made by the Government do not run according to the procedure, meaning that they have not had a deterrent impact on online gambling actors.